Duplication of 9p24.3 in three unrelated patients and their phenotypes, considering affected genes, and similar recurrent variants - Capkova, Zuzana; Capkova, Pavlina; Srovnal, Josef; Adamova, Katerina; Prochazka, Martin; Hajduch, Marian (Molecular genetics & genomic medicine, 2021)
BACKGROUND: Recent studies suggest that duplication of the 9p24.3 chromosomal locus, which includes the DOCK8 and KANK1 genes, is associated with autism spectrum disorders (ASD), intellectual disability/developmental delay (ID/DD), learning problems, language disorders, hyperactivity, and epilepsy. Correlation between this duplication and the carrier phenotype needs further discussion. METHODS: In this study, three unrelated patients with ID/DD and ASD underwent SNP aCGH and MLPA testing. Similarities in the phenotypes of patients with 9p24.3, 15q11.2, and 16p11.2 duplications were also observed. RESULTS: All patients with ID/DD and ASD carried the 9p24.3 duplication and showed intragenic duplication of DOCK8. Additionally, two patients had ADHD, one was hearing impaired and obese, and one had macrocephaly. Inheritance of the 9p24.3 duplication was confirmed in one patient and his sibling. In one patient KANK1 was duplicated along with DOCK8. Carriers of 9p24.3, 15q11.2, and 16p11.2 duplications showed several phenotypic similarities, with ID/DD more strongly associated with duplication of 9p24.3 than of 15q11.2 and 16p11.2. CONCLUSION: We concluded that 9p24.3 is a likely cause of ASD and ID/DD, especially in cases of DOCK8 intragenic duplication. DOCK8 is a likely causative gene, and KANK1 aberrations a modulator, of the clinical phenotype observed. Other modulators were not excluded.
Keywords: Chromosome Duplication; Female; Phenotype; lidské chromozomy, pár 9; dítě; předškolní dítě; Adaptor Proteins, Signal Transducing; ženské pohlaví; chromozomální poruchy; výměnné faktory guaninnukleotidů; adaptorové proteiny signální transdukční; cytoskeletální proteiny; lidé; duplikace chromozomů; Guanine Nucleotide Exchange Factors; Chromosomes, Human, Pair 9; Cytoskeletal Proteins; Male; Developmental Disabilities; Child, Preschool; vývojové poruchy u dětí; Child; fenotyp; mužské pohlaví; Chromosome Disorders; Humans